On-site performance evaluation of a 1, 000-litre microbial fuel cell system using submergible multi-electrode modules with air-cathodes for sustainable municipal wastewater treatment and electricity generation. (6th April 2023) - Heinrichmeier, J.; Littfinski, Tobias; Vasyukova, Ekaterina; Steuernagel, Leon; Wichern, Marc
Abstract: The reliability of a microbial fuel cell (MFC) system was tested on an industrial scale by operating a 1, 000-L single-chamber system under real conditions at a municipal wastewater treatment plant (WWTP) over a 6-month period. Submergible multi-electrode modules with large-scale grid-segmented gas diffusion cathodes with activated carbon as a catalyst were used. Maximum power densities normalised to the cathode area were above 100 mW m −2 Cat . Fluctuating chemical and physical wastewater characteristics of the influent had reversible effects on MFC performance in terms of energetic efficiency. Thereby, the composition of the chemical oxygen demand (COD) fractions changes only insignificantly and the concentration of readily biodegradable ( SS ) required for the enhanced biological phosphorus removal (EBPR) process or upstream denitrification was reduced by 41 ± 10 mg L −1 (37 ± 2% of inflow SS ). HIGHLIGHTS: A 1, 000-L air-cathode microbial fuel cell (MFC) reactor was operated over a 6-month period in a municipal wastewater stream. Large-scale raster segmented air-cathodes in submersible modules for retrofit into primary settling tanks. Determination of COD fraction changes by MFC prior to EBPR and upstream denitrification. Evaluation of rain weather influence on MFC performance and recovery. Graphical Abstract